2017
DOI: 10.1039/c7ta00398f
|View full text |Cite
|
Sign up to set email alerts
|

Three-dimensional photocatalysts with a network structure

Abstract: The synthetic strategies and energy and environmental applications of 3D network photocatalysts are summarized and the ongoing challenges and perspectives are highlighted.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
39
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 100 publications
(39 citation statements)
references
References 205 publications
0
39
0
Order By: Relevance
“…So far, CNs with various morphologies from 0D, 1D, 2D to 3D have been designed [8] , among which carbon nitride aerogel (CNA) or hydrogel (CNH) with 3D hierarchical structure are one of the most outstanding candidates thanks to their interconnected open-framework that could expose more reactive sites, provide convenient mass transfer channels and then promote the surface chemical reaction. Aiming at this goal, different strategies have been presented.…”
mentioning
confidence: 99%
“…So far, CNs with various morphologies from 0D, 1D, 2D to 3D have been designed [8] , among which carbon nitride aerogel (CNA) or hydrogel (CNH) with 3D hierarchical structure are one of the most outstanding candidates thanks to their interconnected open-framework that could expose more reactive sites, provide convenient mass transfer channels and then promote the surface chemical reaction. Aiming at this goal, different strategies have been presented.…”
mentioning
confidence: 99%
“…Catalytic supramolecular hydrogels provide a promising solution to this challenge. [15][16][17][18][19] Hydrogel networks can address the solubility problem because hydrophobic aromatic compounds oen associate into the nanober network in water and become reactively accessible. 20 For example, the Meijer 21 and Escuder 22 groups have shown that a self-assembled, 1D ber network enhances catalytic activity compared to its non-assembled counterpart.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, there have been a great number of works reporting a new generation of composite photocatalysts with 3D frameworks [115]. Actually, the 3D photocatalysts with well-deigned frameworks show great advantages such as a large specific surface area, high adsorptive capacity, good structure stability, good mass transfer ability, and a large number of exposed active sites, which make them promising candidates for the highly efficient photodegradation of contaminants in water.…”
Section: Framework (3d)mentioning
confidence: 99%